2020
DOI: 10.1038/s41598-020-67488-3
|View full text |Cite
|
Sign up to set email alerts
|

Nitrative DNA damage in lung epithelial cells exposed to indium nanoparticles and indium ions

Abstract: indium compounds have been widely used in manufacturing displays of mobile phones, computers and televisions. However, inhalation exposure to indium compounds causes interstitial pneumonia in exposed workers and lung cancer in experimental animals. 8-Nitroguanine (8-nitroG) is a mutagenic DNA lesion formed under inflammatory conditions and may participate in indium-induced carcinogenesis. In this study, we examined 8-nitroG formation in A549 cultured human lung epithelial cells treated with indium compounds, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…HMGB1 is a nuclear protein that is released from dead cells [ 39 ]. We have previously shown that indium compounds induced inflammation-mediated DNA damage in lung epithelial cells via the HMGB1 pathway [ 40 ]. In addition, by binding to toll-like receptor (TLR) 4, HMGB1 activates myeloid differentiation (MyD) 88 and NF-κB essential modulator (NEMO), and activates inflammatory cytokines such as IL-6 and TNF-α via nuclear factor-kappa B (NF-κB) [ 16 , 17 , 18 , 41 , 42 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…HMGB1 is a nuclear protein that is released from dead cells [ 39 ]. We have previously shown that indium compounds induced inflammation-mediated DNA damage in lung epithelial cells via the HMGB1 pathway [ 40 ]. In addition, by binding to toll-like receptor (TLR) 4, HMGB1 activates myeloid differentiation (MyD) 88 and NF-κB essential modulator (NEMO), and activates inflammatory cytokines such as IL-6 and TNF-α via nuclear factor-kappa B (NF-κB) [ 16 , 17 , 18 , 41 , 42 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genotoxicity of indium, in distinct speciation as compared to its speciation in present study, has been reported in the literature. Not only indium oxide and indium tin oxide particles and nanoparticles but also indium chloride have been reported to be genotoxic via the comet assay, micronucleus assay, and measurement of 8-nitroguanine DNA lesion (Tabei et al, 2018 ; Ahmed et al, 2020 ; Tsai et al, 2020 ). While Tsai et al ( 2020 ) attribute indium-related genotoxicity to oxidative stress and mitochondrial dysfunction, Ahmed et al ( 2020 ) rather attribute it to inflammation that triggers 8-nitroguanine formation in the DNA of exposed cells.…”
Section: Discussionmentioning
confidence: 99%
“…Not only indium oxide and indium tin oxide particles and nanoparticles but also indium chloride have been reported to be genotoxic via the comet assay, micronucleus assay, and measurement of 8-nitroguanine DNA lesion (Tabei et al, 2018 ; Ahmed et al, 2020 ; Tsai et al, 2020 ). While Tsai et al ( 2020 ) attribute indium-related genotoxicity to oxidative stress and mitochondrial dysfunction, Ahmed et al ( 2020 ) rather attribute it to inflammation that triggers 8-nitroguanine formation in the DNA of exposed cells. Tabei et al ( 2018 ) demonstrate that indium genotoxicity is not linked with oxidative stress but that it can be related to intracellular degradation of the indium-containing particles, which leads to accumulation of In(III) ions in the nuclei of exposed cells and direct interaction of indium with the DNA.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of carcinogenicity of ITO has been investigated in laboratory animals and it was found that indium compounds including nanoparticles of In 2 O 3 , ITO, and indium chloride (InCl 3 ) significantly increased 8-Nitroguanine (8-nitroG; a mutagenic DNA lesion) formation and stimulated inflammation-mediated DNA damage in lung epithelial cells via the HMGB1-RAGE-TLR9 pathway which may contribute to genotoxicity in the respiratory system 65 .…”
Section: Dmentioning
confidence: 99%